Pertanggungjawaban Pidana Pelaku Tindak Pidana Korupsi Pengelolaan Anggaran Desa Balunijuk (Studi Putusan Nomor 38/Pid.Sus-Tpk/2023/Pn Pgp) - Munte, Hanni Nurhazizah; Manik, Jeanne Darc Noviayanti; Robuwan, Rahmat (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
Criminal liability is defined as the continuation of objective blame that exists in a criminal act and subjectively meets the requirements to be punished for the act. Corruption is regulated in Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption as amended and supplemented by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption. Legal certainty is the basis for a State in implementing applicable laws or regulations. Judges impose sentences based on the principles of justice, legal certainty, and benefit. The study aims to determine and analyze criminal liability and the basis for the judge's considerations in Decision Number 38/Pid.Sus-TPK/2023/PN Pgp. The legal research method in this study is normative legal research. The results of the study showed that M met the elements of criminal liability. The basis of the judge's consideration is that there are aggravating and mitigating reasons. This study concludes that M committed the crime of corruption by fulfilling the elements of error and elements of illegality.